2003
DOI: 10.1126/science.1083328
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Hippocampal Neurogenesis for the Behavioral Effects of Antidepressants

Abstract: Various chronic antidepressant treatments increase adult hippocampal neurogenesis, but the functional importance of this phenomenon remains unclear. Here, using genetic and radiological methods, we show that disrupting antidepressant-induced neurogenesis blocks behavioral responses to antidepressants. Serotonin 1A receptor null mice were insensitive to the neurogenic and behavioral effects of fluoxetine, a serotonin selective reuptake inhibitor. X-irradiation of a restricted region of mouse brain containing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

153
3,288
30
63

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,911 publications
(3,534 citation statements)
references
References 33 publications
153
3,288
30
63
Order By: Relevance
“…This suggest that increases in hippocampal volume observed after long‐term antidepressant treatment are likely mediated through the activation of neurogenic pathways, as opposed to solely a reduction in neuronal cell death. However, our AHN gene set was not enriched for genes predictive of antidepressant response, suggesting that in contrast to non‐human animal findings (Santarelli et al, 2003), AHN may not be the cellular mechanism governing therapeutic response to SSRIs in humans. There are, however, a number of alternative interpretations to this finding.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…This suggest that increases in hippocampal volume observed after long‐term antidepressant treatment are likely mediated through the activation of neurogenic pathways, as opposed to solely a reduction in neuronal cell death. However, our AHN gene set was not enriched for genes predictive of antidepressant response, suggesting that in contrast to non‐human animal findings (Santarelli et al, 2003), AHN may not be the cellular mechanism governing therapeutic response to SSRIs in humans. There are, however, a number of alternative interpretations to this finding.…”
Section: Discussioncontrasting
confidence: 59%
“…However, due to the inaccessible nature of hippocampal progenitor cells in patients, there has been no conclusive evidence directly supporting this relationship in humans. Furthermore, based on convincing non‐human animal data, AHN has been implicated as a cellular mechanism governing antidepressant action (Santarelli et al, 2003) but this, to our knowledge, has yet to be demonstrated in humans.…”
Section: Introductionmentioning
confidence: 99%
“…This supports recent findings indicating an important role of the hippocampus in depression and in the antidepressant response to pharmacotherapy. 52,53 Also, altered size and impaired function of the hippocampus have been found in a number of recent clinical imaging studies of major depression (for a meta-analysis see Campbell 54 ). Furthermore, expression changes in genes implicated in the second messenger systems, such as kinases, phosphatases and the adenylate cyclase 8 gene (ADCY8) were observed in the hippocampus, supporting previous evidence of synaptic plasticity alterations in mood disorders 55,56 and in antidepressant response beyond the neurotransmitter and receptor level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, robalzotan is an effective antagonist of postsynaptic 5-HT 1A receptors in laboratory animals and in humans (Johansson et al, 1997;Andree et al, 2003). Such receptors are believed to play an important role in the antidepressant response of serotonergic agents (Blier and Ward, 2003;Santarelli et al, 2003).…”
Section: Discussionmentioning
confidence: 99%